From Helper to Supervisor: Career Advancement Based on Meritocracy and Islamic Work Values - Putranto, Johni Harius (Perisai : Islamic Banking and Finance Journal, 2026)
Career advancement is an important mechanism to improve employee motivation, productivity, and organizational sustainability. However, in many small and medium enterprises (SMEs), promotion systems are often informal and vulnerable to subjectivity. This study investigates how meritocracy and Islamic work values influence internal career advancement at PT. M steel structure manufacturing company in Sidoarjo. The company applies a structured internal hierarchy consisting of helper, machine operator, coordinator operator, and production supervisor. Promotion decisions are based on job rotation experience, technical competence, communication skills, and responsibility. This study employed a mixed-method approach involving all 35 employees through census sampling and interviews with management. Quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), while qualitative findings supported contextual interpretation. The results indicate that competence, empowering leadership, self-efficacy, and Islamic work values significantly affect career advancement. Transparent merit-based systems were also found to strengthen employee trust and work motivation. This study contributes to the literature of Islamic Human Resource Management by demonstrating the practical relevance of amanah (trustworthiness), kafa’ah (competence), and fairness in promotion systems within manufacturing SMEs. Keywords: Career Advancement, Meritocracy, Islamic HRM, Empowering Leadership, Competence, SMEs